Age demographics and economic growth : a study of Sweden and Finland 1960-2020 - Lyrvall, Martin (SLU/Dept. of Economics, 2022)
This thesis explores the subject of age demographics and economic growth, measured in GDP per capita, in Sweden and Finland between 1960-2020. The chosen method was to compile a number of variables that aim to explain how the age demographics are affected in the two countries and was analysed using OLS-regression. Three different regressions were complied, one for each nation and one that attempts to account for global external factors such as global economic trends and technological change. The results depict that age demographics is correlated with economic growth in Finland and when accounting for confounding factors. This might lead to future problems as the age demographics continue to develop. Over time there might be a shift in government spending and on the labour markets.